Group 2 innate lymphoid cell proportions are diminished in young helminth infected children and restored by curative anti-helminthic treatment. - Norman Nausch; Laura J Appleby; Alexandra M Sparks; Nicholas Midzi; Takafira Mduluza; Francisca Mutapi (PLoS Neglected Tropical Diseases)
Background Group 2 Innate lymphoid cells (ILC2s) are innate cells that produce the TH2 cytokines IL-5 and IL-13. The importance of these cells has recently been demonstrated in experimental models of parasitic diseases but there is a paucity of data on ILC2s in the context of human parasitic infections and in particular of the blood dwelling parasite Schistosoma haematobium. Methodology/principal findings In this case-control study human peripheral blood ILC2s were analysed in relation to infection with the helminth parasite Schistosoma haematobium. Peripheral blood mononuclear cells of 36 S. haematobium infected and 36 age and sex matched uninfected children were analysed for frequencies of ILC2s identified as Lin-CD45+CD127+CD294+CD161+. ILC2s were significantly lower particularly in infected children aged 6-9 years compared to healthy participants. Curative anti-helminthic treatment resulted in an increase in levels of the activating factor TSLP and restoration of ILC2 levels. Conclusion This study demonstrates that ILC2s are diminished in young helminth infected children and restored by removal of the parasites by treatment, indicating a previously undescribed association between a human parasitic infection and ILC2s and suggesting a role of ILC2s before the establishment of protective acquired immunity in human schistosomiasis.